Pembentukan Komunitas “Gema Hijrah” (Generasi Muda Musholla Hijrotul Munawarah) sebagai Model Pemberdayaan Pemuda dalam Memakmurkan Musholla - Khoirul Anwar; Ach. Nizam Rifqi (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The musholla (Islamic prayer room) serves as a strategic center for worship, religious education, and community empowerment. However, limited youth participation has hindered its potential to function as a sustainable center for youth development. This community service program aimed to establish GEMA HIJRAH (Generasi Muda Musholla Hijrotul Munawarah) as a youth empowerment model for revitalizing the musholla through organizational strengthening and the development of a sustainable work program. The program employed a Participatory Action Research (PAR) approach consisting of needs assessment, coordination with the musholla management, youth socialization, organizational establishment, organizational structuring, work program development, mentoring, and monitoring and evaluation. The program resulted in the establishment of GEMA HIJRAH with a structured organizational governance system and a 2026–2028 work program covering organizational development, religious activities, public relations and publication, facilities management, and administration and finance. The initiative increased youth participation in religious and community activities and produced the GEMA Model (Gathering, Empowering, Mobilizing, and Advancing) as a replicable framework for youth empowerment in community-based religious institutions.